Analisis Interaksi Guru dan Siswa Dalam Pembelajaran IPS di Kelas VII di SMPN 3 Balung - Fania Sella Farahma; Raihan Arfiansyah Putra; Rohid Bahrul Fatoni; Muh. Rifqi Bachtiar (Lembaga Pengembangan Kinerja Dosen, 2024)
Abstract. This study looks at how teachers use the social studies method in Class VII of SMP Negeri 3 Balung Jember. The results show that this method is very effective in creating an interactive and supportive learning environment. The constructivism approach, used by teachers, encourages students to build knowledge through active interaction with material and fellow students. Clear instructions and reflection on previous lessons are used to begin the lesson. Then, the use of analogies and interesting learning tools such as videos and educational games are used. Teachers encourage students to actively participate in learning by helping them overcome problems without providing immediate solutions. In-depth questions and timely feedback improve teacher-student communication, creating a dynamic learning environment. This method was successful in increasing students' understanding, technology skills, and their participation. In addition, teachers use preventive and responsive approaches in classroom management to overcome disruptions and create a disciplined and conducive learning environment. Student response to this teaching method was very positive; they are very enthusiastic and very involved.